Tracking Success of African American Landowners in Wabaunsee County, Kansas, Circa 1900: A Case Study of African American Farmers at the Turn of the Century - Spachek, Michael (Kansas State University, The Chapman Center for Rural Studies, 2015)
This paper explores the history of the Kansas Fever Exodus of 1879 and profiles four African American farmers in Wabaunsee County: Franklin Glass, Daniel Swagerty, W. B. Officer, and George Rodman. Contrary to the common historical narrative, many Exodusters enjoyed prosperity and success as farmers.
Michael Spachek, “Tracking Success of African American Landowners in Wabaunsee County, Kansas, Circa 1900: A Case Study of African American Farmers at the Turn of the Century,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/236.
Keywords: Wabaunsee County; Exodusters; Eskridge; Mill Creek Township; tenant farming; Alma Township